2014
DOI: 10.5860/lrts.58n2.84
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Information Needs of Large-Scale Digital Library Users

Abstract: A growing number of large-scale digital libraries, portals that aggregate millions of digitized or born-digital items of historical, cultural, or educational value that are organized into digital collections, have been developed in recent decades. While many of these large-scale digital libraries have been created for the general public, some serve more specific audiences of scholars and educators in different disciplines or domains, for example, history, science, technology, engineering, and mathematics (STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Research is needed to understand the use and role of features in domain‐specific DLs (Zavalina & Vassilieva, ). Understanding the experiences users derive from features (e.g., unexpected, delightful) may provide insights into motivations behind feature use and further inform the design of DLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is needed to understand the use and role of features in domain‐specific DLs (Zavalina & Vassilieva, ). Understanding the experiences users derive from features (e.g., unexpected, delightful) may provide insights into motivations behind feature use and further inform the design of DLs.…”
Section: Discussionmentioning
confidence: 99%
“…Through a comparison of search logs of two domain‐specific DLs—the National Science DL and Opening History—Zavalina and Vassilieva () found there were differences in the ways in which the two research communities searched (e.g., length and type of search queries). However, the examination was limited to the use of input features (e.g., basic keyword, advanced search) rather than the whole SUI, which the current paper examines.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as underlined by Zavalina & Vassilieva (2014), very few studies examine the content of the user search queries and other relevant log files. Ceccarelli et al (2011) used Europeana query logs, but more as means for developing assistance functionalities such as a query recommender system than as objects of study per se.…”
Section: Related Workmentioning
confidence: 99%
“…A number of studies were conducted with educators to evaluate the functionality of the NSDL, its support for designing learning activities, and to examine usage patterns (Recker 2006;Recker et al 2007;Xu and Recker 2012). More recently, Zavalina and Vassilieva (2014) analyzed search queries in the NSDL and Opening History (OH), an aggregator of digital collections with a focus on US history and developed through IMLS National Leadership Grants. The authors found that user searching differed between those two domain-specific DLs in regard to query lengths, frequencies, and search categories.…”
Section: Use Studies Of Large-scale Dlsmentioning
confidence: 99%